Perspectives in Myrtaceae evolution from plastomes and nuclear phylogenies - Balbinott, Natalia (2022)
Myrtaceae is a large and species-rich family of woody eudicots, with prevalent distribution in the Southern Hemisphere. Classification and taxonomy of species belonging to this family is quite challenging, sometimes with difficulty in species identification and producing phylogenies with low support for species relationships. Most of the current knowledge comes from few molecular markers, such as plastid genes and intergenic regions, which can be difficult to handle and produce conflicting results. Based on plastid protein-coding sequences and nuclear markers, we present a topology for the phylogenetic relationships among Myrtaceae tribes. Our phylogenetic estimate offers a contrasting topology over previous analysis with fewer markers. Plastome phylogeny groups the tribes Syzygieae and Eucalypteae and individual chloroplast genes produce divergent topologies, especially among species within Myrteae tribe, but also in regard to the grouping of Syzygieae and Eucalypteae. Results are consistent and reproducible with both nuclear and organellar datasets. It confronts previous data about the deep nodes of Myrtaceae phylogeny.